The intricate link between galaxy dynamics and intrinsic shape (or why so-called prolate rotation is a misnomer). Issue Volume 14:Issue S353(2019) (June 2019) - Foster, Caroline; Bassett, Robert
Abstract: Many recent integral field spectroscopy (IFS) survey teams have used stellar kinematic maps combined with imaging to statistically infer the underlying distributions of galaxy intrinsic shapes. With now several IFS samples at our disposal, the method, which was originally proposed by M. Franx and collaborators in 1991, is gaining in popularity, having been so far applied to ATLAS 3D, SAMI, MANGA and MASSIVE. We present results showing that a commonly assumed relationship between dynamical and intrinsic shape alignment does not hold in Illustris, affecting our ability to recover accurate intrinsic shape distributions. A further implication is that so-called "prolate rotation", where the bulk of stars in prolate galaxies are thought to rotate around the projected major axis, is a misnomer.